2022
DOI: 10.3390/ijerph19148834
|View full text |Cite
|
Sign up to set email alerts
|

Night Shift Work Is Associated with Reduced Rate of Humoral Response Following Vaccination for HBV

Abstract: Night shift work has been associated with cardiovascular and metabolic disease, endocrine and immunological disorders. Published studies have reported that a reduced total sleep time with sleep-wake cycle alterations were associated with a reduced rate of humoral response following vaccination. Our study aimed to evaluate the association between night shift work and serological status for HBV among workers employed in a university hospital in Rome. We evaluated medical records of 986 HCWs working at Tor Vergat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Circadian variation may have a significant impact on the response to vaccination in people who work or train in areas where there is a higher risk of HBV infection, such as healthcare workers and medical students [ 12 , 13 , 14 , 15 , 16 , 17 ]. In Italy, HBV vaccination is mandatory at birth age for all individuals born after the year 1991, but published studies have shown that the percentage of young individuals who are unprotected at the time of their first employment screening is high [ 12 , 14 ], raising questions about the effectiveness and duration of protection in those vaccinated at age <12 months and highlighting the need of a booster dose in these unprotected individuals. The response to a booster dose is generally high in previously vaccinated individuals, demonstrating the persistence of immune memory; however, a lack of response may occur in a variable percentage of individuals, posing a serious safety issue for these individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Circadian variation may have a significant impact on the response to vaccination in people who work or train in areas where there is a higher risk of HBV infection, such as healthcare workers and medical students [ 12 , 13 , 14 , 15 , 16 , 17 ]. In Italy, HBV vaccination is mandatory at birth age for all individuals born after the year 1991, but published studies have shown that the percentage of young individuals who are unprotected at the time of their first employment screening is high [ 12 , 14 ], raising questions about the effectiveness and duration of protection in those vaccinated at age <12 months and highlighting the need of a booster dose in these unprotected individuals. The response to a booster dose is generally high in previously vaccinated individuals, demonstrating the persistence of immune memory; however, a lack of response may occur in a variable percentage of individuals, posing a serious safety issue for these individuals.…”
Section: Introductionmentioning
confidence: 99%